Analisis Pemetaan Potensi Daerah Di Kabupaten Dompu Nusa Tenggara Barat - Putri Wulandari Atur Rezeki (Puslatbang KHAN, 2018)
Dompu Regency is one of the regions with low GDRP in NTB Province. Until 2016, Agriculture, Forestry, and Fishing contributes more than 35% of GDRP. To find out whether the sector is a leading sector in Dompu Regency, more in-depth analysis is needed. The mapping of potential areas in Dompu will be carried out by using Klassen Typology analysis. Based on this analysis for Quadrant I are Construction; Wholesale and Retail Trade, Repair of Motor Vehicles and Motorcycles. Included in Quadrant II are Mining and Quarrying; Manufacturing Industry; Electricity and Gas; Transportation and Storage; Accomodation and Food Service Activities; Information and Communication; Financial and Insurance Activities; Real Estate Activities; Business Activities; Education; Human Health and Sosial Work Activities. Included in Quadrant III are Agriculture, Forestry, and Fishing; and Public Administration and Defence, Compulsory Sosial Security. Included in Quadrant IV are Water Supply, Sewerage, Waste Management and Remediation; and Other Services Activities. We recomended to optimize for developing the economic potential in Dompu Regency by promotion and expansion for Quadrant I, intensification for Quadrant II, extensification for Quadrant III